The benefits of early child development programs: an economic analysis - Van der Gaag, Jacques; Tan, Jee-Peng
Contents :Benefit-Coast analysis of ECD programs,the economics benefits of education,other benefits from education,benefits that are not education-related,an example: the bolivian PIDI program
Keywords: Desarrollo Social; Educación